Keterlibatan Ayah dalam Praktik Pengasuhan Anak (Parenting) Pada Keluarga Urban di Kota Denpasar - Naufal, Muhammad Irfan (Peneliti.net, 2025)
The practice of parenting in a family is always carried out by the mother, while the father's role in the family is as the backbone, serving as the breadwinner. Thus, the father's role in parenting is rarely involved due to work commitments, especially in urban areas. The purpose of this research is to discuss the role of fathers in the involvement of child-rearing practices in urban families in Denpasar City, Bali Province, in shaping children's behavior patterns. The research approach is qualitative phenomenology. This research was conducted in May – June 2024 in the city of Denpasar, South Denpasar District, Kepaon Indah Housing. Qualitative data collection techniques. The data analysis technique in this study is an interactive model consisting of data reduction, data presentation, and conclusion. Based on the research, there are factors that influence fathers in practicing child-rearing. The practice of child-rearing carried out by fathers consists of Parental Engagement, Parental Accessibility,, and Parental Responsibility. From the child-rearing practices conducted by fathers, the parenting styles can be categorized accordingly